Robust analogizing and the outside view: two empirical tests of case‐based decision making - Lovallo, Dan; Clarke, Carmina; Camerer, Colin (Strategic Management Journal, 2012)
Abstract Executives use analogies to improve strategic decisions. However, existing research provides little guidance on the types and number of analogies that produce the best decisions. We examine models of analogy and present findings from two empirical tests. The first test, a study of private‐equity investment decisions, finds that an ‘outside view’—forming a reference class of analogies—performs better than a few analogies familiar to the decision maker. The second test, a study of film revenue forecasts, compares a new model we call similarity‐based forecasting (SBF) with existing methods. The study finds that SBF, which combines elements of reference class forecasting and case‐based decision making, produces better forecasts than regression models. We discuss the consequences of our findings for research and practice. Copyright © 2012 John Wiley & Sons, Ltd.